What makes parents act and react? Parental views and considerations relating to 'child health' during infancy. (December 2017) - Almqvist-Tangen, Gerd; Arvidsson, Susann; Alm, Bernt; Bergman, Stefan; Roswall, Josefine; Dahlgren, Jovanna; Nevonen, Lauri
Lifestyle factors and behaviours are adopted very early in life and tend to persist throughout life. Considering that the parents are the primary gatekeepers for their child's health, there is a need to gain more knowledge and deeper understanding about what causes parents to act and react in order for early preventive efforts to have any effect. The aim was to explore the parental views and considerations concerning 'child health' among parents with infants 8–10 months old. The sample was strategic and 16 parents (aged 23–41) were recruited from three child health centres in Sweden. Open-ended interviews were conducted and a qualitative, manifest content analysis approach was utilized. The parents described the subject 'child health' as a large, multifaceted concept. Three categories emerged during data analysis: developing a sixth sense, being affected by perceptions and believing health and ill health as a continuum. The parents perceived food and feeding issues as one of the most worrying aspects and a significant indicator of 'child health'. In order to meet the parents on their turf, the 'healthy health message' conveyed needs to take the parental perspective into consideration rather than attempting to educate the parents from predetermined assumption, belief and values.